ASPEK SOPAN SANTUN UJARAN DALAM FILM KINGSMAN KARYA MATTHEW VAUGHN: SUATU ANALISIS PRAGMATIK - Suoth, Mita; Pelealu, Hetty; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â  This research entitles â€œAspek Sopan Santun Ujaran dalam Film Kingsman Karya Matthew Vaughn: Suatu Analisis Pragmatikâ€. In this research, the writer focuses on the polite utterance as one aspect of behavior which is found in the film Kingsman. The aims of this research are to identify and classify the kinds of maxims as well as to analyze the functions of maxims used in the film Kingsman. The writer categorized them into their suitable maxims using the theory of Leech (1983). The method used in this study is a descriptive method. In collecting the data the writer has watched 6 times Kingsman film which is the object of this research. The result of this research shows that based on the theory of Leech (1983), there are six kinds of maxims, namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. There are 3 utterances that function as tact maxim, 6 utterances that function as generosity maxim, 11 utterances that function as approbation maxim, 5 utterances that function as modesty maxim, 4 utterances that function as agreement maxim, 3 utterances that function as sympathy maxim. It is expected that this study can help the students and readers in learning politeness aspects of using language.Keywords: Politeness Aspects, Pragmatic, Film Kingsman